Rocky substrate affects benthic heterobranch assemblages and prey/predator relationships. (31st October 2021) - Canessa, M.; Bavestrello, G.; Cattaneo-Vietti, R.; Furfaro, G.; Doneddu, M.; Navone, A.; Trainito, E.
Abstract: During the last twenty years, several studies have demonstrated the primary role of the lithological properties of hard substrates in conditioning the diversity and structure of marine sessile communities (aka bio-mineralogy). This research was dedicated to testing whether different substrates (limestones and granites) influence higher levels of the trophic net. For this purpose, the diversity and abundance of heterobranch molluscs were used to test the hypothesis that their distribution could mirror their prey. The study was conducted in the 'Tavolara-Punta Coda Cavallo' Marine Protected Area (NE Sardinia, Mediterranean Sea), where substrates of different lithology co-occur in a restricted area. Diversity and abundance of heterobranchs were investigated by photographic sampling (3300 studied images) in twelve sites (six limestones and six granites), between 35 and 50 m depth, demonstrating clear preferences of several species for a specific substrate, while others are ubiquitarian. In general, diversity and abundance were higher on limestones due to the exclusive presence of Sacoglossa coupled with a more significant number of Cladobranchia and Doridina; on the other hand, Umbraculida were strongly granite-selected. In some cases, the different affinity of each species was clarified by the distribution of their food sources, but, in others, it is possible to hypothesise that the structure of the whole benthic community, affected by the substrate characteristics, may drive the heterobranchs' distribution. Highlights: Lithology (limestone vs granite) drives the marine benthic communities' structure. The influence of the substrate may reach higher levels of the trophic nets. Diversity and abundance of heterobranchs were higher on limestone than on granite. The distribution of some heterobranchs directly mirrors that of their prey. The occurrence of some species results by the general community complexity.